PERENCANAAN KOMPETENSI KEWIRAUSAHAAN SISWA DI SMKN 1 KARAWANG - Annida Inna Mutmainnah; Ilham Fahmi; Chairil Fajar Hadiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the development of student entrepreneurship competence at SMKN 1 Karawang, viewed from the management functions of planning, organizing, actuating, and evaluation. Vocational high school graduates are expected to be both work-ready and able to create their own business opportunities, so that a directed and sustainable school management of entrepreneurship becomes strategically important. This research used a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation involving the principal, the vice principal for curriculum, the head of the Teaching Factory, the entrepreneurship subject teacher, and students. Data were analyzed using the Miles and Huberman interactive model, covering data collection, data reduction, data display, and conclusion drawing. The findings show that, in the planning aspect, the principal formulates entrepreneurship programs through the Kewirausahaan/KIK subject, the Teaching Factory, and proposals for government assistance oriented toward local-wisdom-based products. In the organizing aspect, duties are distributed among teachers, the Teaching Factory coordinator, and the BLUD manager according to their respective expertise. In the actuating aspect, students experience learning by doing through production, marketing, digital promotion, bazaars, and industry partnerships. In the evaluation aspect, the principal conducts direct field monitoring and uses product sales as an indicator of program success. These four management functions work together to strengthen students' creativity, innovation, and courage in taking business risks.